The Effect of Company Size, Operating Profit/Loss, and Reputation of KAP Auditor on Audit Delay - Muhammad Ridwan Tikollah; Samsinar Samsinar (Program Pascasarjana Universitas Negeri Makassar, 2019)
This associative-causal study aimed determine the effect of company size, operating profit/loss, and reputation of the Public Accountant Firm (Kantor Akuntan Publik/KAP) auditor on audit delay, simultaneously and partially; and which of both variables dominantly affect audit delay of banking companies listed on the Indonesia Stock Exchange (IDX). The research population was all banking companies listed on the IDX, while the samples were 30 banking companies taken by purposive sampling technique. Data collection was done by documentation techniques. Data analysis was carried out by: (1) data test (classic assumption test), and (2) hypothesis test, including: multiple linear regression analysis, F test, and t test. The results showed: (1) company size, operating profit/loss, and reputation of KAP auditor simultaneously affect audit delay, (2) company size had a negative effect on audit delay, thus the larger size of the company would need shorter time on audit delay; the profit/loss of the company had a positive effect audit delay, thus when the company was profit would need longer time on audit delay; reputation of KAP auditor had no effects on audit delay, thus Big Four KAP and non Big Four KAP carried our audit need the same period time; (3) company size had a dominant effect on audit delay, thus the auditors carried out audit dominantly affected by company size.